Study of Non-Targeted Effects Induced on Cell Lines Using Low Doses of Ionizing Radiation - Caires, Hugo R. (2015)
The LNT - Linear-no-Threshold model, used to analyze dose-effect ratios after biological irradiation exposures, theorizes that effects produced are directly proportional to the irradiating doses, with a linear without threshold pattern. Nevertheless, there is a relevant number of evidence, accumulated essentially over the last decade, suggesting that risks inherent to low doses of irradiation cannot be strictly predicted by the LNT model. Among those, there is a significant number of experimental evidence for a variety of low dose induced biological phenomena, which seems to have an impact on modulating the shape of dose-effect curves, namely for expositions below 0.2 Sv, causing the deviation of LNT model. Accumulated evidence demonstrate that cell irradiation induces biological effects, both to directly irradiated cells as well as to cells not exposed to any kind of ionizing radiation, present in a mixed population. This assumption is breaking the classical idea, based on the belief that damage to cellular DNA is only induced by purely ionizing events in cells directly irradiated. This phenomenon, based on cell communication pathways, is termed “Bystander Effect” - clearly highlighted between the “non-targeted effects” of irradiation not considered by the LNT model - being considered one of the biggest paradigm shifts of modern radiobiology.